The viscosity approximation method for multivalued G-nonexpansive mappings in Hadamard spaces endowed with graphs - Bancha Panyanak (2020)
© 2020, Springer Nature Switzerland AG. Using the viscosity approximation method introduced by Moudafi (J Math Anal Appl 241:46–55, 2000), we can obtain strong convergence theorems for monotone increasing G-nonexpansive mappings in Hadamard spaces endowed with graphs. We also give sufficient conditions for the existence of solutions of the variational inequality problem in this setting. Our results generalize and improve many results in the literature.